2016
DOI: 10.1242/dev.137190
|View full text |Cite
|
Sign up to set email alerts
|

Endosperm turgor pressure decreases during early Arabidopsis seed development

Abstract: In Arabidopsis, rapid expansion of the coenocytic endosperm after fertilisation has been proposed to drive early seed growth, which is in turn constrained by the seed coat. This hypothesis implies physical heterogeneity between the endosperm and seed coat compartments during early seed development, which to date has not been demonstrated. Here, we combine tissue indentation with modelling to show that the physical properties of the developing seed are consistent with the hypothesis that elevated endosperm-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Endosperm cellularization is likely to be required for embryonic cell division and growth, since all the mutants that fail to cellularize the endosperm show embryo arrest (Sørensen et al ., ; Ingouff et al ., ). Whether this is due to reduced sugar levels (Hehenberger et al ., ) or elevated turgor pressure (Beauzamy et al ., ) is not clear. However, culturing fis2 or sweet11;12;15 embryos in high sucrose can partially rescue their growth defects (Hehenberger et al ., ; Chen et al ., ).…”
Section: Discussionmentioning
confidence: 95%
“…Endosperm cellularization is likely to be required for embryonic cell division and growth, since all the mutants that fail to cellularize the endosperm show embryo arrest (Sørensen et al ., ; Ingouff et al ., ). Whether this is due to reduced sugar levels (Hehenberger et al ., ) or elevated turgor pressure (Beauzamy et al ., ) is not clear. However, culturing fis2 or sweet11;12;15 embryos in high sucrose can partially rescue their growth defects (Hehenberger et al ., ; Chen et al ., ).…”
Section: Discussionmentioning
confidence: 95%
“…This equipment allows the measurement of the force necessary to carry out tissue indentations of known amplitude using a geometrically defined probe. We carried out 30 µm indentations of immobilised seeds using a flat, circular probe with a diameter of 100 µm as described by Beauzamy et al (2016). Slopes of forcedisplacement curves for the extend-and retract-phases of indentation are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This does not occur in zou Comparison of the apparent stiffness of wild-type and zou-4 mutant seeds at different developmental stages. Stiffness values were extracted from the late linear extend phase of force-displacement curves obtained using a nanoindenter as described by Beauzamy et al, (2016). Effects of osmotic treatment (0.7 M mannitol for 90 min) on seed stiffness are shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed development involves the coordinated growth of maternal seed coat tissues and the enclosed zygotic endosperm and embryo. In oilseed rape and Arabidopsis, it has been demonstrated that the accumulation of high concentrations of hexoses and other soluble metabolites may decrease the osmotic potential of cells in endosperm and other tissues to drive water uptake [32, 33]. Early seed expansion and growth arrest are associated with the rise and drop of endosperm-derived turgor pressure [33].…”
Section: Discussionmentioning
confidence: 99%